Raman spectroscopic study of two dimensional polymer compounds of 2-aminopyrimidine - AKYÜZ, SEVİM; AKYÜZ, ZEKİ TANIL (ELSEVIER SCIENCE BV, PO BOX 211, 1000 AE AMSTERDAM, NETHERLANDS, 2005)
The Raman spectra of the two dimensional layered polymer compounds, M(2APM)(2)M' (CN)(4) {where M = Mn or Cd; and M' = Ni or Pt; 2APM = 2-aminopyrimidine} are reported in the 70-4000 cm(-1) region. Vibrational data suggests that compounds are similar in structure to the Hofmann type two dimensional coordination polymer compounds, formed with M'(CN)(4)(-2) ions bridged by M(2APM)(2)(+2) cations. 2-Aminopyrimidine was coordinated to M(II) through one of the nitrogen atom of its heterocycle ring. Vibrational assignments are given for the bands arising from the tetracyanometallate layers and coordinated 2APM. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: aminopyrimidine; Hofmann type complexes; infrared and Raman spectra; tetracyanonickelate; tetracyanoplatinate; transition metal; metal-complexes; pyrimidine; spectra; IR; halides; aminopirimidin; Hofmann tipi kompleksler; Kızılötesi ve Raman spektrumları; geçiş metali; metal kompleksleri; pirimidin; spektrumları; halojenürler